2018
DOI: 10.1007/s11250-018-1642-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat stress on the behavioral and physiological patterns of Small-tail Han sheep housed indoors

Abstract: This study was conducted to investigate the effects of heat stress on the behavioral and physiological patterns in Small-tail Han sheep housed indoors in summer without climate control. Sixteen adult animals were allocated into two groups of eight animals, based on sex: one group of eight rams and one group of eight ewes. Temperature-humidity index (THI) was used to assess the degree of heat stress. All sheep were subjected to a 10-day pre-experimental period of habituation to the experimental feed and environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 23 publications
1
21
1
4
Order By: Relevance
“…The results of the concentration of the hormone cortisol indicate a variation in the metabolic rate as a result of the variation in the concentration of the cortisol hormone. This is agree with (17) showed that the decrease in the concentration of the hormone cortisol in the ewe blood plasma contributed to reducing the metabolic rate and thus reducing heat production, while it works to increase metabolic rates. This result is agree with (18) referred absence of significant differences in the weight increase between the shearing off and non-shear groups, despite the recording of mathematical differences that indicated that the shear group gave a higher weight than the non shear group.…”
Section: Resultssupporting
confidence: 92%
“…The results of the concentration of the hormone cortisol indicate a variation in the metabolic rate as a result of the variation in the concentration of the cortisol hormone. This is agree with (17) showed that the decrease in the concentration of the hormone cortisol in the ewe blood plasma contributed to reducing the metabolic rate and thus reducing heat production, while it works to increase metabolic rates. This result is agree with (18) referred absence of significant differences in the weight increase between the shearing off and non-shear groups, despite the recording of mathematical differences that indicated that the shear group gave a higher weight than the non shear group.…”
Section: Resultssupporting
confidence: 92%
“…Fewer studies have been performed on HTR4 with regard to body temperature regulation, but it has been shown in animals to exert important regulatory effects in gastrointestinal sensitivity, memory, and food intake, among others [23]. Under heat stress, sheep exhibited reduced food intake and rumination activities, which further reduced the amount of heat generated by metabolism so as to maintain a stable body temperature [6,9]. During this period, HTR4 might play a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term high temperatures and excessively warm weather generate serious heat stress for animals. Heat stress directly or indirectly affects animal physiology, production, and health, among others [1,2,3], which is manifested by physiological features such as gasping for breath, accelerated respiration, elevated heart rate, rising rectal temperature, increasing in-vivo oxidative metabolism, and water and electrolyte disturbance [4,5,6,7]. Regarding reproduction, it can also cause reduced food intake, weight loss, and declining fertility [8,9,10], as well as declining immunity and disease resistance [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-four male sheep carcasses (8 mon of age, Small-Tail Han sheep) with the same feeding system (drylot feeding with the same commercial diet) were randomly collected at a local commercial abattoir in Hebei, China. The Small-Tail Han sheep is a predominant local sheep variety and widely raised in many provinces of China, which originated from Mongolia Sheep and carefully cultivated for a long time in northern China ( Li et al, 2018 ). The 54 carcasses were allocated randomly to three groups for sampling in pre-rigor (45 min postmortem), rigor mortis (24 h postmortem) and post-rigor (72 h postmortem) with 18 carcasses in each group.…”
Section: Methodsmentioning
confidence: 99%